Practice of urban dances in school context: memory and attention of schoolchildren aged 7 and 8 years old (Práxis Educativa, 2023)
This experimental study, with quantitative focus and longitudinal cutting, aimed to verify possible changes in the memory and attention of students aged 7 and 8 years with the practice of urban dances in school. The final sample consisted of 65 students divided into an intervention and control group, submitted to two cognitive tests. In the first test, the control group reached in the pre and post-test, respectively, an average of 19.9 (Standard Deviation – SD = 1.98) and 19.2 (SD = 2.33), while the intervention group reached, respectively, 19.4 (SD = 2.47) and 21.5 (SD = 2.50) (p